Chairman's government background, excess employment and government subsidies: Evidence from Chinese local state-owned enterprises - Wang Xiongyuan; Wang Shan (China Journal of Accounting Research, 2013)
Local state-owned enterprises (SOEs) in China continue to face government interference in their operations. They are influenced both by the government's "grabbing hand" and by its "helping hand." Our study examines how SOE chairmen with connections to government influence their firm's employment policies and the economic consequences of overstaffing. Using a sample of China's listed local state-owned enterprises, we find that the scale of overstaffing in these SOEs is negatively related to the firms' political connections to government. However, this relationship turns positive when the firm's chairman has a government background. Appointing chairmen who have government backgrounds is a mechanism through which the government can intervene in local SOEs and influence firms' staffing decisions. We also find that in compensation for the expenses of overstaffing, local SOEs receive more government subsidies and bank loans. However, the chairmen themselves do not get increased pay or promotion opportunities for supporting overstaffing. Further analysis indicates that whereas the "grabbing hand" of government does harm to a firm's economic performance, the "helping hand" provides only weak positive effects, and such government intervention actually reduces the efficiency of social resource allocation.
Keywords: D73; G28; G32; H2; 650; Government background; Excess employment; Government intervention